ENDOSCOPIC SLEEVE GASTROPLASTY - MINIMALLY INVASIVE THERAPY FOR PRIMARY OBESITY TREATMENT - GALVÃO-NETO,Manoel dos Passos (2016)
ABSTRACT Background: Less invasive and complex procedures have been developed to treat obesity. The successful use of Endoscopic Sleeve Gastroplasty using OverStitch(r) (Apollo Endosurgery, Austin, Texas, USA) has been reported in the literature. Aim: Present technical details of the procedure and its surgical/ endoscopic preliminary outcome. Method: The device was used to perform plications along the greater curvature of the stomach, creating a tubulization similar to a sleeve gastrectomy. Result: A male patient with a BMI of 35.17 kg/m2 underwent the procedure, with successful achievement of four plications, and preservation of gastric fundus. The procedure was successfully performed in 50 minutes, time without bleeding or other complications. The patient presented mild abdominal pain and good acceptance of liquid diet. Conclusions: The endoscopic gastroplasty procedure was safe, with acceptable technical viability, short in duration and without early complications.